Urine assay for tenofovir to monitor adherence in real time to tenofovir disoproxil fumarate/emtricitabine as pre‐exposure prophylaxis. Issue 6 (26th April 2017) - Koenig, HC; Mounzer, K; Daughtridge, GW; Sloan, CE; Lalley‐Chareczko, L; Moorthy, GS; Conyngham, SC; Zuppa, AF; Montaner, LJ; Tebas, P
Abstract : Objectives: Tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) is approved for pre‐exposure prophylaxis (PrEP) against HIV infection. Adherence is critical for the success of PrEP, but current adherence measurements are inadequate for real‐time adherence monitoring. We developed and validated a urine assay to measure tenofovir (TFV) to objectively monitor adherence to PrEP. Methods: We developed a urine assay using high‐performance liquid chromatography coupled to tandem mass spectrometry with high sensitivity/specificity for TFV that allowed us to determine TFV concentrations in log10 categories between 0 and 10 000 ng/mL. We validated the assay in three cohorts: (1) HIV‐positive subjects with undetectable viral loads on a TDF/FTC‐based regimen, (2) healthy HIV‐negative subjects who received a single dose of TDF/FTC, and (3) HIV‐negative subjects receiving daily TDF/FTC as PrEP for 24 weeks. Results: The urine assay detected TFV with greater sensitivity than plasma‐based measures and with a window of measurements within 7 days of the last TDF/FTC dose. Based on the urine log‐linear clearance after the last dose and its concordance with all detectable plasma levels, a urine TFV concentration > 1000 ng/mL was identified as highly predictive of the presence of TFV in plasma at > 10 ng/mL. The urine assay was able to distinguish high and low adherence patterns within the last 48 h (> 1000 ng/mL versus 10–1000 ng/mL), as well as nonadherence (< 10 ng/mL) extended over at least 1 week prior to measurement. Conclusions: We provide proof of concept that a semiquantitative urine assay measuring levels of TFV could be further developed into a point‐of‐care test and be a useful tool to monitor adherence to PrEP.